Energy Conversion by Parallel Electric Fields During Guide Field Reconnection in Scaled Laboratory and Space Experiments. Issue 23 (7th December 2018) - Fox, W.; Wilder, F. D.; Eriksson, S.; Jara‐Almonte, J.; Pucci, F.; Yoo, J.; Ji, H.; Yamada, M.; Ergun, R. E.; Oieroset, M.; Phan, T. D.
Abstract: We present direct and scaled comparisons between laboratory and in situ space observations of magnetic reconnection with a guide field, comparing results from the Magnetospheric Multiscale Mission and the Magnetic Reconnection eXperiment (MRX). While Magnetospheric Multiscale Mission observations obtain high‐resolution and fully kinetic data, MRX observations fully cover the 2‐D reconnection plane near the current sheet, removing uncertainties in situating the measurements compared to the reconnection region. Through scaling transformations, we show a quantitative agreement in magnetic field and current density profiles, which agree within a factor of 2 from each other. The introduction of the guide field causes the energy conversion J ·E in the current sheet to be dominated by J || E || in both cases. However, parallel electric fields reported by recent spacecraft crossings are significantly (5–10 times) larger than values obtained on MRX, highlighting an important issue for understanding energy conversion by reconnection. Plain Language Summary: Magnetic reconnection is an important process in the Earth's magnetosphere which rapidly converts magnetic field energy to kinetic energy in the plasma. It is studied both in situ by spacecraft such as the Magnetospheric Multiscale Mission and laboratory experiments. Directly comparing the two is important because the different experiments provide complementary insights about the same process. We find scaling transformations which allow direct comparisons of the results of the experiments, showing agreement on fundamental quantities, such as the width of the current sheet, and also interesting areas of disagreement, especially noting the extremely large electric fields and associated enhanced energy dissipation observed by Magnetospheric Multiscale Mission. These results prompt new questions about nature of energy conversion in space current sheets. Key Points: Direct scaled comparisons between space and laboratory plasmas show common structure of reconnection current sheets with a guide field During guide field reconnection the energy conversion is dominated by J || E || in both experiments